1998
DOI: 10.1046/j.1365-2427.1998.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term recovery of a mountain stream from clear‐cut logging: the effects of forest succession on benthic invertebrate community structure

Abstract: 1. Changes in benthic invertebrate community structure following 16 years of forest succession after logging were examined by estimating benthic invertebrate abundance, biomass and secondary production in streams draining a forested reference and a recovering clear‐cut catchment. Benthic invertebrate abundance was three times higher, and invertebrate biomass and production were two times higher in the disturbed stream. 2. Comparison of invertebrate community abundance 1, 5 and 16 years after clear‐cutting indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
179
5
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(195 citation statements)
references
References 47 publications
9
179
5
2
Order By: Relevance
“…Previous studies showed similar positive effects of large-scale forest harvesting on benthic invertebrate abundances (Stone and Wallace, 1998;Kiffney et al, 2003;Haggerty et al, 2004). Favorable habitat conditions and greater energy availability may stimulate the production of tolerant invertebrates and thus total invertebrate abundance in recently harvested stream reaches (Ely and Wallace, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies showed similar positive effects of large-scale forest harvesting on benthic invertebrate abundances (Stone and Wallace, 1998;Kiffney et al, 2003;Haggerty et al, 2004). Favorable habitat conditions and greater energy availability may stimulate the production of tolerant invertebrates and thus total invertebrate abundance in recently harvested stream reaches (Ely and Wallace, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…However, litter processiag rates (Benfield et al 2001, Griffith and Perry 199 1, Webstcr and Waide 1982), litter retention (Speaker et al 1984, Webster et al 1994) and invertebrate production and abundance in lotic systems (Stone andWallace 1998, Stout et al, 1993) have been well researched. Murphy and Giller (2001) found that factors influencing the structure of detritivore assemblages were important in determining thc rate of detritus processing.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves that have faster conditioning rates are typically consumed first because they are nutritionally suitable more quickly (Kaushik and Hynes, 1971 (Benfield et al 2001, Griffith and Perry 1991. Webster and Waide 1982, litter retention (Speaker et al 1984, Webster et al 1994, and invertebrate production rates (Stone andWallace, 1998, Stout ct al. 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Tree fall also increases the light availability and the biomass of benthic algae (major food source for several invertebrates, Robinson & Minshall 1986). Stone and Wallace (1998) observed that after tree fall autochthonous production of organic matter can exceed allochthonous inputs, with strong changes in the invertebrates assemblages.…”
Section: Fauna Composition and Stream Characteristicsmentioning
confidence: 99%
“…The increase in field size and the destruction of riparian vegetation also induce an increase in fine sediment inputs into streams (Stevens & Cummins 1999, Quinn & Stroud 2002, with potential stream bed clogging (Culp et al 1983, Quinn et al 1992, Hancock 2002, changes in the chemical characteristics of interstitial water (Dahm et al 1998) and in the composition of interstitial assemblages (Boulton et al 1998). The destruction of riparian woody buffer generates a decrease in leaf litter inputs (Stone & Wallace 1998, Mc Kie & Cranston 2001, that modifies community composition (decrease of shredders), but increases light availability for aquatic vegetation and phytophilous invertebrates (increase in habitat availability; Habbija et al 2002). Even in forests, human activities (like logging) induce an increase in sediments inputs into streams by soil scouring (Benfield et al 2001, Collier & Smith 2005 or through road construction (Sidle et al 2004), with changes in the composition of invertebrate communities and in organic matter availability (Webster & Waide 206 (2) 1982).…”
Section: Introductionmentioning
confidence: 99%